1956
DOI: 10.1111/j.1464-410x.1956.tb04791.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Herpes Zoster With Involvement of the Urinary Bladder1

Abstract: SUMMARY A case of herpes zoster is described in which the third and fourth sacral segments were involved on the left side, and in which an eruption on the left side of the bladder was accompained by retention of urine. Thirteen other case reports have been reviewed in which bladder symptoms complicated sacral zoster. There appears to be an inverse relation between the severity of the bladder eruption and the incidence of retention of urine, and this may be explicable on the basis of variable spread of the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Urinary retention is acute and appears to be concordant with skin rashes [10] . In the present case, a urodynamic study in the acute stage revealed detrusor areflexia which completely improved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Urinary retention is acute and appears to be concordant with skin rashes [10] . In the present case, a urodynamic study in the acute stage revealed detrusor areflexia which completely improved.…”
Section: Discussionmentioning
confidence: 99%
“…Richmond [13] reported that cord level involvement in urinary retention due to herpes zoster was sacral in 78%, thoracolumbar in 11% and high thoracic in 11% of patients. It was suggested that the inflammatory reaction involving the dorsal root ganglia may spread proximally and distally to the sacral segments of the spinal cord, interrupting the detrusor reflex [10,13,14,20] . Although herpes zoster affects both sexes equally [11] , men are reported to be affected more commonly by herpes zoster with bladder involvement [19][20][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herpes Zoster can cause detrusor paralysis when the L5 and sacral segments of the cord are affected. Bladder lesions may be seen at cystoscopy (Gibbon, 1956), and sphincter and bulbocavernosus reflexes are present. It responds to conservative treatment.…”
Section: Miscellaneous Lesionsmentioning
confidence: 99%
“…Urinary retention accompanying sacral herpes zoster has been described in several works [6][7][8]. The skin man ifestations are so characteristic that the diagnosis seldom causes problems.…”
Section: Introductionmentioning
confidence: 99%